Genistein Induces Deleterious Effects during Its Acute Exposure in Swiss Mice. (22nd May 2014) - Singh, Prabhat; Sharma, Sharad; Kumar Rath, Srikanta
Abstract : Genistein is a soy derived isoflavone. It has wide variety of therapeutic effects against certain diseases including cancer. Although toxic effects of genistein have been studied, its effect on the gene expression and the reason behind toxicity have not been identified yet. In the present study, genistein was administered to age and body weight matched Swiss mice at the doses of 125, 250, 500 and 1000 mg/kg. The biomarkers of hepatotoxicity in serum, liver histology, oxidative stress parameters in tissue homogenates, and global gene expression were examined. Elevated alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) levels and degenerated liver tissue were observed in 500, and 1000 mg/kg genistein treated groups. Oxidative stress was significant at these doses as considerable increase in lipid peroxidation (LPO) and decrease in total glutathione (GSH) were observed. Gene expression analysis showed 40 differentially expressed genes at twofold change and P < 0.05. Differentially expressed genes were corresponding to different biologically relevant pathways including metabolic and oxidative stress pathways. In 500 mg/kg group, Cyp4a14, Sult1e1, Gadd45g, Cidec, Mycs, and so forth genes were upregulated. These results suggested that the higher dose of genistein can produce several undesirable effects by affecting multiple cellular pathways.